Students’ Speaking Performances Evaluation in English Webinar Series Activity - Dela Irawan; Dian Susyla; Ria Angraini; Ririn Putri Ananda (UNIVED Press, 2022)
AbstractThe objective of this research is to find out and describe the EnglishStudents’ Speaking Performances in English Webinar Series Activitywhich had been conducted on January 4th – 10th, 2021 with the theme“Teaching and Learning English is Easy, Fun, and Cool”. Theresearch design of this research uses descriptive qualitative method.The instruments used were: (a) The Analytic Rubrics; and (b) thevideo recording from Zoom Meeting Application of students’ speakingwho had followed the English Webinar Series Activity. The result ofthis research showed the English students have a quite good score tomaster the components of speaking performances as fluency,pronunciation, vocabulary, grammar accuracy and comprehension.This research is suggested to English students should understand thecomponents of speaking performances when they perform in publicspeaking.Keywords: Speaking Performances, Evaluation, Webinar Activity.